Pazopanib-induced organizing pneumonia in a patient with leiomyosarcoma: A case report. (2020) - Watanabe, Chie; Miyata, Jun; Esaki, Kotoba; Suematsu, Ryohei; Sano, Tomoya; Yamamoto, Takayuki; Sasaki, Hisashi; Maki, Yohei; Tagami, Yoichi; Kimizuka, Yoshifumi; Fujikura, Yuji; Ito, Keiichi; et al.
Abstract: Pazopanib, a multityrosine kinase inhibitor used for treating malignant soft tissue tumors, rarely causes adverse events associated with the respiratory system. We report a case of a 73-year-old male with leiomyosarcoma treated with pazopanib. Four months after treatment initiation, chest computed tomography showed bilateral patchy consolidation and ground-glass opacities. Bronchoscopy revealed increased lymphocytes in the bronchoalveolar lavage fluid. Histological analysis of lung tissue demonstrated intraluminal fibrotic changes in alveolar spaces. According to these findings, we diagnosed the patient with pazopanib-induced organizing pneumonia. To best of our knowledge, this is the first report of such a case. Highlights: Pazopanib is a multityrosine kinase inhibitor used for treating soft tissue tumors. Pazopanib rarely causes adverse events associated with the respiratory system. This is the first report of a patient with pazopanib-induced organizing pneumonia.